Direitos humanos e (in) tolerância religiosa: laicismo proselitismo fundamentalismo terrorismo - Gonçalves, Antonio Baptista (2011)
The matter involving Human Rights and religious (in) tolerance is in consonance with the current international scenario, and it counts on a number of examples: France and the crisis of the Lay State, Denmark and the Islamic intolerance, conflicts in Palestine and Israel, the use of veil in Turkey are just a few recent cases that raise the debate on religious freedom protection. To discuss the current problems would not be possible without a background of the relation that permeates the religious freedom with the emergence of human rights. Thus, matters involving religion blossom bringing with them their problematic and controversies and always drawing a parallel between religion and human rights we will present the relationship between religion with political power and the controversial church-state relationship. In a way that, the separation between Church and Estate will provide the study of our first issue: secularism and laic procedure. Religion has always used artifices to gather new believers and, therefore, we will deepen the study of the religious proselytism and the defense of multiculturalism and of minorities. Finally, we approach the delicate issue of fundamentalism and how religion has contributed negatively to originate terrorism. Moreover, we will also deal with countermeasures adopted by the Human Rights and which is the current relationship between religion and human rights